Implementasi Kebijakan dalam Meningkatkan Sumber Daya Aparatur Pemerintahan di Kantor Kecamatan Bintauna Kabupaten Bolmong Utara - Tabo, Sarfan (Gorontalo Journal of Public Administration Studies, 2018)
This study aims to determine or analyze the implementation of government policy in Bintauna District Office. Through research observation will be able to get a picture or explanation about the implementation of policy towards empowerment of government apparatus in District Office of Bintauna. This research is a descriptive research concerning two main things that is as the main insight, the first focuses on the actual problems that come from the apparatus that became the respondent. This objective and effort is to optimally capture the facts in the field so as to obtain data from this research proportionally and reveal various problems related to the government apparatus in implementing government policy concepts in Bintauna District Office of North Bolmong Regency as well as the extent of their implementation. From the research that has been done found the lack of attention, coaching as well as direction by the leadership on the discipline of the apparatus. But if judged from the overall results, it can be concluded that the policies implemented by the district government succeed. Because if calculated from the percentage of frequencies in the table recapitulation, the percentage of efforts to improve the quality of the apparatus is above average.